"Hola, my name is Carmen, who is this?"- Language ideologies and dialect stylization in prank calls. Issue 2 (3rd April 2021) - Loza, Sergio; Vana, Rosti
ABSTRACT: This study discusses the dialect stylization and language ideologies involved in a nationally broadcasted radio prank show, Carmen Call s. This national prank show permits a discussion on the language practices and hegemonic ideologies involved in the media representation of the show's Latina protagonist; Carmen Santiago De la Hoya Ruiz Rivera Perez Tú Sabes . This exaggerated radio persona utilizes various linguistic and ideological mechanisms such as mock Spanish, code-switching, and other specific dialect features to create stylistic performances of Latinx stereotypes to harass unsuspecting victims. This study considers how the framing of the radio show draws upon the current socio-historical context of the U.S. in an era of escalading anti-immigrant and, therefore, anti-bilingual sentiment to create both the persona and the prank calls themselves. The analysis shows how the pranks draw from preexisting socio-cultural profiles and repertoires to reinforce monolingualism, nationalist ideologies, and dominant discourses regarding Latinx people. By bringing into the fold dominant semiotic and values associated with Latinxs, the show is able to employ them to project the vulgar, inappropriate, and hypothetical Carmen persona that upholds mainstream discourses through the same discriminatory practices that are part of U.S. Spanish-speakers' lived experiences as minority language users.